2003
DOI: 10.1080/00207590244000250
|View full text |Cite
|
Sign up to set email alerts
|

Even statisticians are not immune to misinterpretations of Null Hypothesis Significance Tests

Abstract: W e investigated the way experienced users interpret Null Hypothesis Significance Testing (NHST) outcomes. An empirical study was designed to compare the reactions of two populations of NHST users, psychological researchers and professional applied statisticians, when faced with contradictory situations. The subjects were presented with the results of an experiment designed to test the efficacy of a drug by comparing two groups (treatment/placebo). Four situations were constructed by combining the outcome of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 39 publications
3
40
0
6
Order By: Relevance
“…In fact, Mittag and Thompson (2000), Gordon (2001), and Lecoutre, Poitevineau, and Lecoutre (2003) convincingly showed that even statisticians are not immune to misconceptions about hypothesis tests. For more than twenty years, misconceptions and misuses regarding hypothesis tests have been documented (an historical summary of bad practices can be found in Daniel 1998).…”
Section: Misconceptions About Hypothesis Testsmentioning
confidence: 99%
“…In fact, Mittag and Thompson (2000), Gordon (2001), and Lecoutre, Poitevineau, and Lecoutre (2003) convincingly showed that even statisticians are not immune to misconceptions about hypothesis tests. For more than twenty years, misconceptions and misuses regarding hypothesis tests have been documented (an historical summary of bad practices can be found in Daniel 1998).…”
Section: Misconceptions About Hypothesis Testsmentioning
confidence: 99%
“…Although the focus of the significance testing debate has centered on the theoretical arguments for or against it, some research has focused on the interpretation of significance testing outcomes in practice (e.g., Lecoutre et al, 2003;Oakes, 1986;Rosenthal & Gaito, 1963;Weisburd, Lum, & Yang, 2003). For example, Finch et al (2001) focused on misconceptions about significance testing as revealed in published reports.…”
mentioning
confidence: 99%
“…ej., Badenes-Ribera et al, 2015;Badenes-Ribera et al, 2016;Haller & Kraus, 2002;Monterde-iBort et al, 2010;Oakes, 1986), en muestras de miembros de la American Educational Research Association (AERA) (p. ej., Mittag & Thompson, 2000) y en profesionales de la Estadística (Lecoutre, Poitevineau, & Lecoutre, 2003).…”
Section: Discussionunclassified